ANALISIS PERILAKU EKONOMI RUMAH TANGGA PETANI JAGUNG DI DESA BANYUBANG BERDASARKAN PERSPEKTIF EKONOMI ISLAM - Ah Miftahul Alim; Asfi Manzilati (Islamic Economics and finance in Focus, 2024)
The research aims to understand the economic behavior of farmer households based on Islamic economic views. So that it can provide a broader perspective on how to address economic problems, especially in rural areas by considering the principles of justice, sustainability, and balance between worldly and spiritual needs. Quantitative methods with descriptive analysis and average difference tests as analytical tools. The analysis results show that the economic behavior of farmer households in Banyubang village in terms of income comes mostly from corn production, around 37% of farmers have off-farm income and 29% of farmers have non-farm income. After testing, the results were obtained that there were differences in the consumption of farmer households in Banyubang Village before and after harvest. The condition of economic behavior of farmer households in Banyubang Village is based on the Islamic economic perspective, it can be seen that farmer households implement production and consumption activities based on Islamic law, such as producing halal goods, using capital free from usury and farmer households in Banyubang Village live economically without being wasteful and allocate income for needs in accordance with Islamic law such as zakat, infaq and shodaqoh.